2003
DOI: 10.1002/ejlt.200390013
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of wild and cultivated gilthead seabream (Sparus aurata) and sea bass (Dicentrarchus labrax)

Abstract: Short communicationTotal lipid content and fatty acid composition were determined for wild and cultivated gilthead seabream and sea bass. Fatty acid analyses were carried out by gas chromatography-mass spectrometry. Respective total lipid content of flesh in cultivated gilthead seabream and sea bass were 1.7-5.0-times those of wild samples. Palmitic acid (C16:0) and oleic acid (C18:1n-9) were the major fatty acids respectively among the saturated fatty acids and monounsaturated fatty acids of each fish species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
14
22
0
1
Order By: Relevance
“…It is indicated that C16:0 is present in a higher ratio in fish tissues and is more stable than C18:0 (Aras et al 2003b). Many fish tissues seem to contain excessive amounts of C18:1 n-9 within the total MUFA (Aras et al 2003a;Saglik et al 2003). Results of our study also supported this phenomenon.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is indicated that C16:0 is present in a higher ratio in fish tissues and is more stable than C18:0 (Aras et al 2003b). Many fish tissues seem to contain excessive amounts of C18:1 n-9 within the total MUFA (Aras et al 2003a;Saglik et al 2003). Results of our study also supported this phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…Various studies on tissue composition of fish and their relationship to human health have been carried out on wild and cultivated fish (Rueda et al 1997(Rueda et al , 2001Saglik et al 2003), rainbow trout (Kiessling et al 2001;Aras et al 2003a;Haliloglu et al 2003) and juvenile fish which were fed different diets (Figueiredo-Silva et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fish lipids are particularly rich in polyunsaturated fatty acids (PUFA). The predominant n-3 fatty acids in marine fish are eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (Sağlık et al, 2003;Özogul et al, 2007).…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Over the last 5 years, a growing interest has been observed in the aquaculture of the Percidae fish, which has resulted in the establishing of new farms focused on the rearing of European perch under controlled conditions (Fontaine & Kestemont, 2008). Various environmental conditions and the different diets of wild and reared fish affect their chemical composition, including their fatty acid profile (Cejas et al, 2004;Grigoriakis, Alexis, Taylor, & Hole, 2002;Periago et al, 2005;Rueda et al, 1997;Saglik et al, 2003;Sèrot, Gandemer, & Demaimay, 1998;Sheik-Eldin, De Silva, Anderson, & Gooley, 1996;Suzuki, Okazaki, Hayakawa, Wada, & Tamura, 1986).…”
Section: Introductionmentioning
confidence: 99%